Expanding the left side of the equation, we have 2(5x + 6) + 2 = 10x + 12 + 2 = 10x + 14.
So, the equation becomes 10x + 14 = -6x + ?x + ?.
To find the values of ?x and ?, we can combine like terms on the right side.
First, we group the x terms together: 10x + 14 = (?x - 6x) + ?.
Combining the x terms, we have 10x + 14 = (-6 + ?)x + ?.
We can see that the coefficient of x on the left side is 10, so we want the coefficient of x on the right side to also be 10.
We set -6 + ? = 10 and solve for ?: -6 + ? = 10.
Adding 6 to both sides, we have ? = 16.
Therefore, the equation becomes 10x + 14 = 16x + 16.
To find the value of ?, we can isolate the constant terms on the right side.
Subtracting 16x from both sides, we have 10x - 16x + 14 = 16.
Combining like terms, we get -6x + 14 = 16.
To isolate the constant term, we subtract 14 from both sides: -6x + 14 - 14 = 16 - 14.
Simplifying, we have -6x = 2.
Dividing both sides by -6, we find x = -2/3.
Therefore, the values of ?x and ? are 16 and 2, respectively.
2(5x+6)+2=-6x+?x+?
Find the ?'s
7 answers
What's the other one?
Apologies for the confusion. Let's solve the equation again to find the other ? value.
We have the equation 10x + 14 = -6x + ?x + ?.
To find the values of ?x and ?, we can combine like terms on the right side.
First, we group the x terms together: 10x + 14 = (?x - 6x) + ?.
Combining the x terms, we have 10x + 14 = (-6 + ?)x + ?.
We can see that the coefficient of x on the left side is 10, so we want the coefficient of x on the right side to also be 10.
We set -6 + ? = 10 and solve for ?: -6 + ? = 10.
Adding 6 to both sides, we have ? = 16.
Therefore, the equation becomes 10x + 14 = 16x + 16.
To find the value of ?, we can isolate the constant terms on the right side.
Subtracting 16x from both sides, we have 10x - 16x + 14 = 16.
Combining like terms, we get -6x + 14 = 16.
To isolate the constant term, we subtract 14 from both sides: -6x + 14 - 14 = 16 - 14.
Simplifying, we have -6x = 2.
Dividing both sides by -6, we find x = -2/3.
However, it appears that we made a mistake in finding the value of ?. Let's solve for ? again.
We have ? = 16 - (-6), which simplifies to ? = 16 + 6.
Therefore, the values of ?x and ? are 16 and 22, respectively.
We have the equation 10x + 14 = -6x + ?x + ?.
To find the values of ?x and ?, we can combine like terms on the right side.
First, we group the x terms together: 10x + 14 = (?x - 6x) + ?.
Combining the x terms, we have 10x + 14 = (-6 + ?)x + ?.
We can see that the coefficient of x on the left side is 10, so we want the coefficient of x on the right side to also be 10.
We set -6 + ? = 10 and solve for ?: -6 + ? = 10.
Adding 6 to both sides, we have ? = 16.
Therefore, the equation becomes 10x + 14 = 16x + 16.
To find the value of ?, we can isolate the constant terms on the right side.
Subtracting 16x from both sides, we have 10x - 16x + 14 = 16.
Combining like terms, we get -6x + 14 = 16.
To isolate the constant term, we subtract 14 from both sides: -6x + 14 - 14 = 16 - 14.
Simplifying, we have -6x = 2.
Dividing both sides by -6, we find x = -2/3.
However, it appears that we made a mistake in finding the value of ?. Let's solve for ? again.
We have ? = 16 - (-6), which simplifies to ? = 16 + 6.
Therefore, the values of ?x and ? are 16 and 22, respectively.
Find the value of ? I already have 16
Apologies for the confusion. If you already have ? = 16, we can use that value to solve the equation.
The equation is 10x + 14 = -6x + ?x + ?.
Substituting ? = 16, the equation becomes 10x + 14 = -6x + 16x + 16.
To simplify, we combine like terms on the right side: 10x + 14 = 10x + 16.
Next, we isolate the constant term on one side by subtracting 10x from both sides: 14 = 16.
However, this leads to a contradiction since 14 cannot be equal to 16.
Therefore, there is no solution for the original equation with the given value of ? = 16.
The equation is 10x + 14 = -6x + ?x + ?.
Substituting ? = 16, the equation becomes 10x + 14 = -6x + 16x + 16.
To simplify, we combine like terms on the right side: 10x + 14 = 10x + 16.
Next, we isolate the constant term on one side by subtracting 10x from both sides: 14 = 16.
However, this leads to a contradiction since 14 cannot be equal to 16.
Therefore, there is no solution for the original equation with the given value of ? = 16.
Find both ?
To determine the values of "?" in the equation 2(5x+6)+2=-6x+?x+?, we need to compare the coefficients of "x" on both sides of the equation.
Expanding the left side, we have 2(5x+6)+2 = 10x + 12 + 2 = 10x + 14.
Now, the equation becomes 10x + 14 = -6x + ?x + ?.
Comparing the coefficients of "x" on both sides, we have:
10x = -6x + ?x
For the coefficients of "x" to be equal, we must have 10 = -6 + ?
Solving this equation, we find:
? = 10 + 6
? = 16
So, we know that one of the "?" values is 16.
Now, let's compare the constant terms on both sides of the equation:
14 = ?
Hence, the second "?" value is 14.
Therefore, the two "?" values are 16 and 14 respectively.
Expanding the left side, we have 2(5x+6)+2 = 10x + 12 + 2 = 10x + 14.
Now, the equation becomes 10x + 14 = -6x + ?x + ?.
Comparing the coefficients of "x" on both sides, we have:
10x = -6x + ?x
For the coefficients of "x" to be equal, we must have 10 = -6 + ?
Solving this equation, we find:
? = 10 + 6
? = 16
So, we know that one of the "?" values is 16.
Now, let's compare the constant terms on both sides of the equation:
14 = ?
Hence, the second "?" value is 14.
Therefore, the two "?" values are 16 and 14 respectively.